Bi2Se3 nanosheets-based photothermal composites with hydrophobic surface for synergistic anti-/de-icing. (1st March 2023) - Zhou, Peng; Wang, Yuyan; Zhang, Xinxing
Abstract: Ice accumulation-induced damage to outdoor equipment such as wind turbine blades, aircraft and weaponry has been a long-standing concern. The traditional two-dimensional (2D) photothermal nanomaterials, which are extensively applied for de-icing, have strong phonon diffusion and high thermal conductivity, causing great heat loss and limit the application in the field of heat retention. Herein, Bi2 Se3 nanosheets with photothermal effect are selected in terms of solar harvesting and heat loss reduction, endowing the composite membrane with outstanding light absorption (over 90%) and low thermal conductivity (0.054 W (mK) −1 ). The real-time conversion of solar-heat-electricity is further recorded, demonstrating an electrical output power density of about 110.5 μW cm −2 . Furthermore, rose petals-like surface is fabricated by using fabric as a template in a scalable way and the slippery coating is prepared via in-situ growth of octadecyltrichlorosilane. Such structural design enables membrane desired hydrophobicity (contact angle 137°), which lead to the shedding of water and melted ice. This kind of anti and de-icing device can provide a valuable guidance for the design of sustainable and intelligent device in the future. Graphical abstract: Schematic illustration of the fabrication process of the photothermal membrane with hydrophobic surface for anti-/deicing, and the solar-heat-electricity conversion system. Image 1